Effects of fermented and unfermented aging corn on ruminal fermentation, bacterial communities, lactation performance and plasma metabolites in Holstein cows - X.L. Wang; G.N. Zhang; Y.S. Ma; Y.Q. Wang; J.Z. Lv; G.Z. Feng; M.T. Lambo; Y.G. Zhang (Animal)
Aging reduces the nutritional value of corn grain, which may be improved by fermentation prior to use. This study investigated the effects of replacing conventional corn (CC) with aging corn (AC) and fermented aging corn (FAC) in the diets of lactating Holstein cows. Six healthy third-parity Holstein cows were used in a replicated 3 × 3 Latin square experiment with 21-day periods. Cows were fed twice and milked twice daily. The cows were randomly divided into three treatment groups: (1) CC diet: a diet with 23.6% starch in diet DM containing 24.0% conventional corn; (2) AC diet: a diet with 23.5% starch in diet DM containing 24.0% aging corn replacing conventional corn; and (3) FAC diet: a diet with 23.2% starch in diet DM containing 24.6% fermented aging corn replacing conventional corn. The diets were formulated to be isonitrogenous and contained identical roughage. The FAC treatment increased the starch digestibility compared with AC. Feeding FAC increased the concentrations of total volatile fatty acid compared with CC and AC and decreased the molar proportion of acetate compared with AC. At the family level, the relative abundance of Prevotellaceae was higher on FAC than CC. The relative abundance of Succinivibrionaceae was lower on FAC than on CC and AC. Besides, at the genera level, the relative abundance of Succinivibrionaceae_UCG_002 in the rumen was higher on AC than CC and FAC. The relative abundance of Prevotella and Ruminococcus was higher on FAC than CC and AC. The relative abundance of Succinivibrionaceae_UCG_001 was lower on FAC than CC. The Simpson index was lower on FAC than CC and AC. The FAC treatment increased the milk yield (34.0, 33.7, and 35.2 kg/d for CC, AC, and FAC group, respectively) and protein yield, and thus, energy-corrected milk production was increased, and at the same time, decreased the somatic cell score compared with CC and AC. The AC treatment increased the malondialdehyde concentration in plasma compared with CC and FAC. The concentrations in plasma of triglyceride and malondialdehyde were lower on FAC than AC. The immunoglobulin G concentration in plasma was higher on FAC than CC and AC. Overall, feeding AC resulted in decreased plasma antioxidant capacity compared with CC, whereas feeding FAC altered the relative abundance of bacteria in the rumen and improved starch digestibility, ruminal bacterial diversity, lactation performance, plasma antioxidant capacity and immune competence compared with AC in dairy cows.